Achieving Functional Outcomes after Surgical Management of Catastrophic Vasopressor-induced Limb Ischemia. Issue 3 (March 2022) - Deldar, Romina; Abu El Hawa, Areeg A.; Haffner, Zoe K.; Higgins, James P.; Katz, Ryan D.; Attinger, Christopher E.; Evans, Karen K.
Abstract : Background: Vasopressor-induced limb ischemia is an unfortunate complication that can occur in patients treated for septic shock. Current literature lacks surgical treatment recommendations for this condition, besides amputation. We describe various reconstructive surgeries and functional outcomes in patients treated surgically for vasopressor-induced limb ischemia. Methods: We retrospectively reviewed patients who were treated for septic shock and developed vasopressor-induced limb ischemia at our tertiary referral academic medical center. We reviewed presentation, treatment, surgical outcomes, and long-term functional outcomes. Results: We present three previously healthy patients who developed gangrene of multiple limbs following the use of vasopressors to treat septic shock. Each patient underwent amputations or limb salvage procedures. Conclusions: Limb ischemia is a devastating complication that can occur after prolonged vasopressor use. The decision to proceed with limb salvage versus amputation of ischemic extremities should be tailored to the individual patient. The main objective should be for the patient to obtain optimal function and quality of life, regardless of the type of surgery.